Sugary Food and Beverages Consumption, Family History, and Primary Dysmenorrhea in Undergraduate Students, Faculty of Public Health, Universitas Indonesia - Raihani Ramadhan; Wahyu Kurnia Yusrin Putra; Diah Mulyawati Utari; Khoirul Anwar (Faculty of Public Health Universitas Indonesia, 2023)
Primary dysmenorrhea is the most common gynecological problem experienced by women of reproductive age and can interfere with daily activities. Therefore, the aim of this study was to determine the prevalence and differences in the proportion of primary dysmenorrhea based on individual factors (duration of menstrual bleeding, family history, physical activity, stress) and diet (breakfast habits, frequency of saturated fat consumption, omega-3 consumption, iron consumption, frequency of consumption of dairy products, caffeine consumption, and frequency of consumption of sugary foods and beverages). This study used a cross-sectional design and involved 150 regular undergraduate students in the 2019-2022 batch of Faculty of Public Health Universitas Indonesia who were selected with a systematic random sampling technique. Data were collected by filling out an online questionnaire and analyzed with chi square test and multiple logistic regression. Results showed that 61.3% of female students experienced primary dysmenorrhea. Bivariate analysis showed that there was a significant difference (p value < 0.05) in the proportion of primary dysmenorrhea based on family history, caffeine consumption, and frequency of consumption of sugary foods and beverages. Multivariate analysis showed that the frequency of consumption of sugary foods and drinks (OR = 4.8) and family history (OR = 4.7) were the two most influencing factors associated with the incidence of primary dysmenorrhea. This study shows that the frequency of consumption of sugary foods and beverages and family history increase the risk of primary dysmenorrhea.